2022
DOI: 10.1093/noajnl/vdac175
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal MR spectroscopy to detect progression in patients with lower-grade glioma in the surveillance phase

Abstract: Background Monitoring lower grade gliomas (LrGGs) for disease progression is made difficult by the limits of anatomical MRI to distinguish treatment related tissue changes from tumor progression. MR spectroscopic imaging (MRSI) offers additional metabolic information that can help address these challenges. The goal of this study was to compare longitudinal changes in multiparametric MRI, including diffusion weighted imaging, perfusion imaging, and 3D MRSI, for LrGG patients who progressed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…A longitudinal measurement in 41 patients with low-grade glioma demonstrated increasing Cho/NAA concentrations in patients who had progression in their tumor grade, suggesting that MRS may be a viable surveillance tool in addition to traditional MRI follow-up. 12 Another study revealed that over the course of 1 year, a decrease in the Cho concentration within the center of the lesion is correlated to the reduction in tumor volume in patients treated with temozolomide, highlighting the value of MRS in monitoring the response to chemotherapy. 13 Furthermore, Cho/Cr measurements have shown 85.5% discrimination accuracy in differentiating between disease recurrence and radiation injury 14 and 84% discrimination accuracy in differentiating between disease recurrence and pseudoprogression.…”
Section: Mr Spectroscopymentioning
confidence: 99%
“…A longitudinal measurement in 41 patients with low-grade glioma demonstrated increasing Cho/NAA concentrations in patients who had progression in their tumor grade, suggesting that MRS may be a viable surveillance tool in addition to traditional MRI follow-up. 12 Another study revealed that over the course of 1 year, a decrease in the Cho concentration within the center of the lesion is correlated to the reduction in tumor volume in patients treated with temozolomide, highlighting the value of MRS in monitoring the response to chemotherapy. 13 Furthermore, Cho/Cr measurements have shown 85.5% discrimination accuracy in differentiating between disease recurrence and radiation injury 14 and 84% discrimination accuracy in differentiating between disease recurrence and pseudoprogression.…”
Section: Mr Spectroscopymentioning
confidence: 99%